Utilization of Instagram by Glamping Legok Kondang Ciwidey as a Promotion Media during the Pandemic - Diniati, Anisa; Salma, Aqida Nuril; Lestari, Martha Tri; Devi, Ni Luh Putu Febriyanti Suntari; Tasliman, Cassey Adela (Institut Pariwisata Trisakti, 2022)
This research aims to describe how social media Instagram that tourism industry players, and the tourists use during the pandemic, can be utilized as a promotion tool so that more people will be interested in traveling again, especially in the era of the new normal. This research uses a qualitative approach with descriptive research type and data collection techniques carried out through in-depth interviews with one key informant, non-participant observation, and document study. The results show that in carrying out its promotion, Glamping Ciwidey utilizes some features of social media Instagram and emphasizes certain content to attract the attention of their target audiences. In modifying the audiences’ behavior, they optimize the ability of the influencer that was involved in building brand awareness and the interest of tourists’ attraction and maximizing the features of posting and reposting content from the influencers also visitors through Insta Story and Instagram Feeds. In providing the information such as product knowledge and persuading the audiences to be interested in visiting, they utilize some of Instagram’s features and emphasize the digital content creation, such as activities and the view around there, the implementation of health protocol, infographic, and repost content. Keywords: Nature Tourism, Promotion Media, Social Media For Tourism Marketing